Studi Penanganan Jalan Amblas di Desa Sumbernanas, Kecamatan Gedangan, Kabupaten Malang - Henri Siswanto; Eddy Triyanto Sudjatmiko (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
A landslide occurred in Sumbernanas village, Gedangan district, Malang regency. This incident caused the 50 m of the road along the Gedangan – Gondanglegi section to collapse as much as 3 m deep. Some repairs were attempted, however it did not bring expected results. This study aims to analyze the causes of the road collapse and develop effective methods of measurement. The research comprise; field observations, study of regional geological conditions, in-situ soil investigations, topographic measurements, data processing and analysis. Design parameters were determined through back-calculation analysis of the stability of the slopes at the time of the collapse. The results indicated that the collapse was caused by the combination of scouring of the river channel banks and soil softening as a result of groundwater infiltration. The proposed measurement method is installation of a gabion construction to function as a retaining wall. Based on structure calculations obtained, the safety factors are (SF)> 1,5 for the short term and SF> 1,1 for the long term.